A Topic Modeling Analysis of Parental Needs for Preterm Infant Feeding Difficulties Using Internet and Social Media Keywords. - Ji, Eun Sun; Chung, Yoon Chung; Noh, Yun Sun; Park, Hui Seon (Inquiry (00469580), 2026)
Introduction: This study aimed to explore parental needs related to feeding difficulties in preterm infants by analyzing keywords and discourse trends from the mobile Internet and social networking services (SNS). Methods: Data were collected from online news, blogs, and SNS platforms in South Korea between January 2020 and December 2024. Text mining, semantic network analysis, and LDA topic modeling were conducted using TEXTOM and NetMiner. Results: A total of 3,904 documents were analyzed. Five major topics were identified: (1) adaptation to early feeding, (2) recognition of feeding problems, (3) medical issues and welfare support, (4) repeated failures and misinformation, and (5) therapeutic interventions. Conclusion: The findings suggest that parental needs regarding preterm infant feeding difficulties require professional training and multidisciplinary support systems.